Sarcopenic Obesity in Adult Patients: Prevalence and Risk Factors - Sana Khamassi; Fatma Boukhayatia; Haifa Abdesselem; Emna Bornaz; Kamilia Ounaissa; Houda Bouhajja; Awatef Kacem; Amel Gammoudi; Rahma Mahjoub; Emna Talbi; Henda Jamoussi; Chiraz Amrouche (Nutrition and Metabolic Insights)
Background: Sarcopenia now constitutes a serious issue that can affect the obese adult population. The aims of our study were to estimate the prevalence of sarcopenia in a group of obese patients, investigate the impact of sarcopenic obesity (SO) on patient health and quality of life, and identify its risk factors. Methods: We conducted a cross-sectional descriptive observational study of a group of obese adult patients. Physical activity was assessed with the Ricci and Gagnon questionnaire and quality of life was evaluated using the SF-12 and ORWELL-97 questionnaires. SO was defined in accordance with the EASO-ESPEN consensus statement. Results: We included 100 patients with a mean age of 44.42 ± 13.25 years. SO was diagnosed in 19% of the study population. The assessment of the impact of SO revealed that it was associated with osteoarthritis ( P  < .0001), functional disability ( P  = .001) and obesity-specific quality of life impairment ( P  < .0001). SO was associated with lower education levels ( P  = .011), a low score in the daily physical activities’ dimension of the Ricci and Gagnon score ( P  = .028), class 2 obesity ( P  = .032), elevated blood triglyceride levels ( P  = .019), potassium and manganese intake deficiency ( P  = .042 and P  = .004, respectively). Non-sarcopenic obese patients had a higher frequency of a history of weight loss interventions ( P  = .038), excess protein intake ( P  = .042), and excess lipid intake ( P  = .011). Multivariate analysis identified class 2 obesity ( P  = .048), osteoarthritis ( P  = .038), elevated triglyceride levels ( P  = .049), manganese deficiency intake ( P  = .026), increased score in the daily physical activities’ dimension ( P  = .048), increased gait speed ( P  = .025) and excess fat intake ( P  = .047) as factors independently associated with SO. Conclusion: It is essential to incorporate the screening for sarcopenia into the therapeutic approach for obese adult patients due to its clinical consequences and impact on individuals’ quality of life.